The heat generation processes in Q-switched YAG:Nd/YAG:Cr microchip laser and their influence on the parameters of laser radiation - Buryy, O.; Ubizskii, S. (Видавництво Львівської політехніки, 2012)
The heat generation processes are considered for passively Q-switched YAG:Nd/YAG:Cr microchip laser. The distributions of the temperature, the refractive index and the deformations of laser crystal are determined. At the given profile of refractive index and deformations of the active element, the laser beam radius and the divergence are calculated.
Keywords: solid-state laser; Q-switched laser; diodepumped lasers; yttrium-aluminium garnet; heat conductivity